The Development Strategy of The Shallot as A Commodty Featured in OKU District - Pakhruddin, Pakhruddin; Munajat, Munajat; Efriyanty, Rini (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
Shallot is the one commodity vegetable featured long been cultivated by farmers in Indonesia. Shallot is also the main commodity in the prioritized development of vegetable lowlands in Indonesia in addition to the already hundreds of years cultivated, as well as is one of the sources of income of farmers and the country's economy. The study aimed to examine whether the shallot is the main commodity in the OKU District and the strategy of developing shallot planting in the OKU District. The research results show that the commodity shallot sub in OKU District with the analysis of the LQ had an index value of 0.42 = LQ < 1. Thus, shallot plantation is a sector in which its production fails to meet the needs of District OKU due to the lack of the role of the sector in the regional economy. It does not have the advantages of the comparative and categorized the non-base or not commodities is a sub-sector of the non-base following the value of LQ < 1. The government conduct management improvement coaching for farmer groups so that institutions in the downstream sector and agribusiness are strong. It is necessary to implement four development strategies to develop shallot planting as a commodity in the OKU District.